Effect of recombinant fibroblast growth factor 10 on the lung vasculature in a mouse model of bronchopulmonary dysplasia - Gersmann, Luisa; Justus Liebig University Giessen (My University, 2025)
There is strong evidence for the essential role of FGF10 during lung development. However, little is known about its concrete effect on the vascular system and the contribution of pulmonary vasculature to the pathogenesis of BPD. We aimed to study the impact of rFGF10 on the vasculature of the lung in a mouse model of BPD, to gain new information about underlying mechanisms and related pathologies such as BPD-PH. To demonstrate the effect of hyperoxia-induced lung injury, we exposed two experimental groups to hyperoxia (HYX) (PN1-PN8) followed by several intraperitoneal injections of PBS or rFGF10 until PN42. In the following experiments, we compared these groups to a control group held under normoxic conditions (NOX). Before lung harvest on PN45, we performed lung function and echocardiographic measurements to study organ function indices. We found strong indications for impaired right ventricular function represented by high TAPSE values in the HYX PBS group, suggesting an increased pressure of the pulmonary vascular system connected downstream of the right ventricle of the heart. The HYX FGF10 group showed a normalization of all studied indices in the functional experiments. Afterward, we collected lungs for further analysis involving RT-qPCR, immunostainings, and vascular morphometry after a double staining with ACTA2 and vWF. In summary, we found increased expression of Vegfa and its receptor Vegfr2 in the qPCR after rFGF10 treatment. The vascular morphometry revealed a rarefication of vessels in the distal areas of the lung after exposure to hyperoxia and regeneration after rFGF10 treatment. Furthermore, we were able to demonstrate an increased percentage of fully muscularized vessels towards a PH-phenotype after HYX lung injury and normalization after rFGF10 treatment in the periphery of the lung. Our results provide evidence for the affection of the pulmonary vasculature in a mouse model of BPD and the beneficial effects of rFGF10 treatment at a late stage of lung development. We found improved organ function, upregulated expression of pro-angiogenic genes and normalized histological features in the HYX FGF10 group compared to the HYX PBS group. In conclusion, this study reveals important information about changes of the pulmonary vasculature after hyperoxic lung injury at PN45, which represents young adulthood of the mice. We were able to partly reverse the damage described with our rFGF10 treatment. These findings might be crucial in developing targeted therapies to prevent or treat BPD and associated vascular comorbidities in prematurely born infants.
Keywords: ddc:610